Evolution of local computing time in parallel modeling of mobile networks - Zhukova, L. F.; Shchur, L. N. (Frontiers in Physics, 2024)
In this paper, we apply the scaling theory of statistical physics to study the properties of a parallel discrete-event simulation model. In this type of parallel computing, each process has a different computation time, known as local virtual time. Local virtual times evolve during the simulation, forming a complex profile similar to surface growth profile in physics. We construct a simple local virtual times evolution algorithm for a primitive mobile network model called a Personal Communication Service system and compare this theoretical time evolution model with a standard implementation of a parallel mobile network in the Rensselaer's Optimistic Simulation System. We show that the value of the critical exponent for the mobile network system is close to the one in the theoretical local virtual time profile model. We believe that the similarities we found can be useful for preliminary analysis of scalability, process desynchronization, and possible deadlocks in a wide class of parallel discrete-event simulation models.